Effective Professional Communication A Rhetorical Approach - Bennetch, Rebekah; Owen, Corey; Keesey, Zachary (Open textbook library., 2021)
Welcome to Effective Professional Communication, your text book for the RCM 200 course at the University of Saskatchewan in Saskatoon, Saskatchewan. As you already know, this course focuses on communicating in professional environments. Even if you haven’t held a job before, you know–at least on a basic level–that how you communicate changes depending on the context of your situation; specifically, you talk differently when you speak to customers/clients versus your co-workers versus your supervisors. Our goal in this text is to break down the communication process in professional environments so you can maximize your chance to get hired and retain your job once you graduate from university. We will do this by looking at communication through political, rhetorical, ethical, and interpersonal lenses and applying this knowledge to your future career.